1974
DOI: 10.1530/jrf.0.0400291
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Components of the Luminal Fluid From the Bovine Uterus

Abstract: Summary. The The possible significance of these uterine-specific proteins on embryonic development and control of luteolysis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…Roberts & Parker (1976) Harrison, Heap, Horton & Poyser (1972) showed that surgical separation of the uterus and the ovaries in the ewe caused the animal to become pseudopregnant and fluid to accumulate in the uterus. A preliminary electrophoretic examination of a specimen of this fluid at pH 3-5 showed prominent protein bands migrating as do the uterine proteins reported by Roberts & Parker (1974a). A similar result is obtained with intact animals treated with large amounts of exogenous progesterone, and the uterine fluid of such animals was therefore investigated more extensively.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Roberts & Parker (1976) Harrison, Heap, Horton & Poyser (1972) showed that surgical separation of the uterus and the ovaries in the ewe caused the animal to become pseudopregnant and fluid to accumulate in the uterus. A preliminary electrophoretic examination of a specimen of this fluid at pH 3-5 showed prominent protein bands migrating as do the uterine proteins reported by Roberts & Parker (1974a). A similar result is obtained with intact animals treated with large amounts of exogenous progesterone, and the uterine fluid of such animals was therefore investigated more extensively.…”
Section: Introductionsupporting
confidence: 75%
“…The exploratory work of Roberts & Parker (1974a) and Laster (1977) has demonstrated that uterine proteins are present in the cow. Initially the uterine washings used by Roberts & Parker (1974a) provided a source of uterine protein but it rapidly became apparent that, with an average yield of 15 mg total protein per uterine washing, of which not more than 300 pg were the materials sought, this source was inadequate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiserum to bovine serum albumin was produced as described previously (Roberts & Parker, 1974). Antisera to tubulin and actin were generously provided by Dr R. A. Badley, who produced them as described previously (Badley et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…This organism has high iron requirements for in vitro cultivation (50-100 μM) [Tachezy et al, 1996], surpassing those of eukaryotic cells, although comparable to other anaerobic amitochondriate protists. T. foetus inhabits the vagina, cervix, and the lumen of the bovine uterus, with the last one being characterized as rich in TF [Roberts and Parker, 1974]. Therefore, TF could be an important source of iron for T. foetus.…”
Section: Tritrichomonas Foetusmentioning
confidence: 99%